Growth disturbance in chronic renal failure: etiology and treatment - Mehls, Otto; Schaefer, Franz; Tönshoff, Burkhard (Pediatric dialysis, 2004)
One of the major somatic consequences and psychological burdens of chronic renal failure (CRF) is the disturbance of body growth. Since the start of dialysis improves renal clearance, it was the hope of patients and clinicians that the improved renal clearance may also result in a better growth rate. Unfortunately, those expectations have not been fulfilled. Furthermore, the time of dialysis is usually too short to correct for a previous height deficit. As a consequence, treatment of growth failure in renal patients should be diagnosed and treated early. Since the majority of children with CRF have congenital renal disorders, the problem of prevention and treatment of growth failure starts immediately after birth.
Gesehen am 29.01.2021